Multi-Omics Characterization of a KIF1C Structural Variant in a Patient with a Complex Movement Disorder Partially Responsive to Deep Brain Stimulation - Mirja Thomsen; Max Borsche; Vicente A. Yépez; Dirk Rasche; Kristian K. Ullrich; Vera Tadic; Saad M. Abdelwakeel; Hauke Busch; Sören Franzenburg; Joanne Trinh; Christine Klein; Katja Lohmann; et al. (The Cerebellum, 2026)
Biallelic KIF1C variants are associated with a spectrum of neurological phenotypes, including spasticity, cerebellar ataxia, chorea, and dystonia. Most reported patients involve single-nucleotide variants, whereas copy number variants (CNVs) have been described only once in the PubMed-listed literature. The therapeutic potential of deep-brain stimulation (DBS) in KIF1C -related disease has not yet been evaluated. We report a patient presenting with spasticity, ataxia, dystonia, and head tremor, in whom prior exome sequencing was inconclusive. A multi-omics approach was applied, including optical genome mapping (OGM), genome sequencing, and transcriptome sequencing. The clinical effect of DBS was assessed. OGM revealed a homozygous KIF1C Exon 17–18 deletion, retrospectively detectable in exome and genome data but initially missed by sequence analysis. Transcriptome sequencing demonstrated significantly reduced KIF1C expression and absence of normally spliced transcripts around those exons, consistent with a loss-of-function mechanism. DBS led to partial clinical improvement, with notable reduction of dystonia and head tremor. Structural variants may be an underrecognized cause of complex movement disorders involving spasticity, ataxia, and dystonia. Diagnostic methods specifically targeting structural variation, such as OGM or CNV analysis of short-read data, can be essential for diagnosis. Transcriptome data add valuable functional insight. This report also suggests that DBS may offer symptomatic benefit in KIF1C -associated disease, particularly for dystonic signs.

Correction to: Picking up speed: cell cycle regulation during effector CD8+ T cell differentiation - Lorenz Kretschmer; Noémie Fuchs; Dirk H. Busch; Veit R. Buchholz (Medical Microbiology and Immunology, 2023)

Picking up speed: cell cycle regulation during effector CD8+ T cell differentiation - Lorenz Kretschmer; Noémie Fuchs; Dirk H. Busch; Veit R. Buchholz (Medical Microbiology and Immunology, 2023)
Clonal expansion and development of immunological memory are two hallmarks of adaptive immune responses. Resolving the intricate pathways that regulate cell cycle activity and lead to the generation of diverse effector and memory T cell subsets is essential for improving our understanding of protective T cell immunity. A deeper knowledge of cell cycle regulation in T cells also has translational implications for adoptive cell therapies and vaccinations against infectious diseases. Here, we summarize recent evidence for an early diversification of effector and memory CD8 + T cell fates and discuss how this process is coupled to discrete changes in division speed. We further review technical advances in lineage tracing and cell cycle analysis and outline how these techniques have shed new light on the population dynamics of CD8 + T cell responses, thereby refining our current understanding of the developmental organization of the memory T cell pool.

Assessment of angiogenesis-related parameters in juvenile idiopathic arthritis-associated uveitis - Karoline Baquet-Walscheid; Lena Wildschütz; Maren Kasper; Martin Busch; Solon Thanos; Dirk Bauer; Monika Stoll; Simone König; Arnd Heiligenhaus (Molecular Biology Reports, 2022)

Rates of bacterial co-infections and antimicrobial use in COVID-19 patients: a retrospective cohort study in light of antibiotic stewardship - Kathrin Rothe; Susanne Feihl; Jochen Schneider; Fabian Wallnöfer; Milena Wurst; Marina Lukas; Matthias Treiber; Tobias Lahmer; Markus Heim; Michael Dommasch; Birgit Waschulzik; Alexander Zink; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)
The coronavirus disease 2019 (COVID-19) caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has spread worldwide. Bacterial co-infections are associated with unfavourable outcomes in respiratory viral infections; however, microbiological and antibiotic data related to COVID-19 are sparse. Adequate use of antibiotics in line with antibiotic stewardship (ABS) principles is warranted during the pandemic. We performed a retrospective study of clinical and microbiological characteristics of 140 COVID-19 patients admitted between February and April 2020 to a German University hospital, with a focus on bacterial co-infections and antimicrobial therapy. The final date of follow-up was 6 May 2020. Clinical data of 140 COVID-19 patients were recorded: The median age was 63.5 (range 17–99) years; 64% were males. According to the implemented local ABS guidelines, the most commonly used antibiotic regimen was ampicillin/sulbactam (41.5%) with a median duration of 6 (range 1–13) days. Urinary antigen tests for Legionella pneumophila and Streptococcus peumoniae were negative in all cases. In critically ill patients admitted to intensive care units ( n = 50), co-infections with Enterobacterales (34.0%) and Aspergillus fumigatus (18.0%) were detected. Blood cultures collected at admission showed a diagnostic yield of 4.2%. Bacterial and fungal co-infections are rare in COVID-19 patients and are mainly prevalent in critically ill patients. Further studies are needed to assess the impact of antimicrobial therapy on therapeutic outcome in COVID-19 patients to prevent antimicrobial overuse. ABS guidelines could help in optimising the management of COVID-19. Investigation of microbial patterns of infectious complications in critically ill COVID-19 patients is also required.

Development of an AAV9-RNAi-mediated silencing strategy to abrogate TRPM4 expression in the adult heart - Rebekka Medert; Andreas Jungmann; Staffan Hildebrand; Martin Busch; Dirk Grimm; Veit Flockerzi; Oliver J. Müller; Patrick Most; Dagmar Schumacher; Marc Freichel (Pflügers Archiv - European Journal of Physiology, 2021)
The cation channel transient receptor potential melastatin 4 (TRPM4) is a calcium-activated non-selective cation channel and acts in cardiomyocytes as a negative modulator of the L-type Ca 2+ influx. Global deletion of TRPM4 in the mouse led to increased cardiac contractility under β-adrenergic stimulation. Consequently, cardiomyocyte-specific inactivation of the TRPM4 function appears to be a promising strategy to improve cardiac contractility in heart failure patients. The aim of this study was to develop a gene therapy approach in mice that specifically silences the expression of TRPM4 in cardiomyocytes. First, short hairpin RNA miR30 (shRNA miR30 ) sequences against the TRPM4 mRNA were screened in vitro using lentiviral transduction for a stable expression of the shRNA cassettes. Western blot analysis identified three efficient shRNA miR30 sequences out of six, which reduced the endogenous TRPM4 protein level by up to 90 ± 6%. Subsequently, the most efficient shRNA miR30 sequences were delivered into cardiomyocytes of adult mice using adeno-associated virus serotype 9 (AAV9)-mediated gene transfer. Initially, the AAV9 vector particles were administered via the lateral tail vein, which resulted in a downregulation of TRPM4 by 46 ± 2%. Next, various optimization steps were carried out to improve knockdown efficiency in vivo. First, the design of the expression cassette was streamlined for integration in a self-complementary AAV vector backbone for a faster expression. Compared to the application via the lateral tail vein, intravenous application via the retro-orbital sinus has the advantage that the vector solution reaches the heart directly and in a high concentration, and eventually a TRPM4 knockdown efficiency of 90 ± 7% in the heart was accomplished by this approach. By optimization of the shRNA miR30 constructs and expression cassette as well as the route of AAV9 vector application, a 90% reduction of TRPM4 expression was achieved in the adult mouse heart. In the future, AAV9-RNAi-mediated inactivation of TRPM4 could be a promising strategy to increase cardiac contractility in preclinical animal models of acute and chronic forms of cardiac contractile failure.

Phenotypic Differences in Primary Murine Microglia Treated with NOD1, NOD2, and NOD1/2 Agonists - Susanne Wasmuth; Tida Viola Jalilvand; Björn Laffer; Martin Busch; Dirk Bauer; Thomas Langmann; Solon Thanos; Maren Kasper; Arnd Heiligenhaus (Journal of Molecular Neuroscience, 2020)

A comprehensive and comparative phenotypic analysis of the collaborative founder strains identifies new and known phenotypes - Heike Kollmus; Helmut Fuchs; Christoph Lengger; Hamed Haselimashhadi; Molly A. Bogue; Manuela A. Östereicher; Marion Horsch; Thure Adler; Juan Antonio Aguilar-Pimentel; Oana Veronica Amarie; Lore Becker; Johannes Beckers; et al. (Mammalian Genome, 2020)
The collaborative cross (CC) is a large panel of mouse-inbred lines derived from eight founder strains (NOD/ShiLtJ, NZO/HILtJ, A/J, C57BL/6J, 129S1/SvImJ, CAST/EiJ, PWK/PhJ, and WSB/EiJ). Here, we performed a comprehensive and comparative phenotyping screening to identify phenotypic differences and similarities between the eight founder strains. In total, more than 300 parameters including allergy, behavior, cardiovascular, clinical blood chemistry, dysmorphology, bone and cartilage, energy metabolism, eye and vision, immunology, lung function, neurology, nociception, and pathology were analyzed; in most traits from sixteen females and sixteen males. We identified over 270 parameters that were significantly different between strains. This study highlights the value of the founder and CC strains for phenotype-genotype associations of many genetic traits that are highly relevant to human diseases. All data described here are publicly available from the mouse phenome database for analyses and downloads.

Innovations in phenotyping of mouse models in the German Mouse Clinic - Helmut Fuchs; Valérie Gailus-Durner; Susanne Neschen; Thure Adler; Luciana Caminha Afonso; Juan Antonio Aguilar-Pimentel; Lore Becker; Alexander Bohla; Julia Calzada-Wack; Christian Cohrs; Anna Dewert; Barbara Fridrich; et al. (Mammalian Genome, 2012)

Targeting the epidermal growth factor receptor (HER) family by T cell receptor gene-modified T lymphocytes - Peter Meyerhuber; Heinke Conrad; Lilian Stärck; Matthias Leisegang; Dirk H. Busch; Wolfgang Uckert; Helga Bernhard (Journal of Molecular Medicine, 2010)

Microphthalmia, parkinsonism, and enhanced nociception in Pitx3 416insG mice - Michael Rosemann; Alesia Ivashkevich; Jack Favor; Claudia Dalke; Sabine M. Hölter; Lore Becker; Ildikó Rácz; Ines Bolle; Martina Klempt; Birgit Rathkolb; Svetoslav Kalaydjiev; Thure Adler; et al. (Mammalian Genome, 2010)

Mycoplasma contamination of murine embryonic stem cells affects cell parameters, germline transmission and chimeric progeny - Kyriaki Markoullis; Diana Bulian; Gabriele Hölzlwimmer; Leticia Quintanilla-Martinez; Katrin-Janine Heiliger; Horst Zitzelsberger; Hagen Scherb; Josef Mysliwietz; Cord C. Uphoff; Hans G. Drexler; Thure Adler; Dirk H. Busch; et al. (Transgenic Research, 2009)

A molecular biological protocol to distinguish potentially human pathogenic Stenotrophomonas maltophilia from plant‐associated Stenotrophomonas rhizophila - Kathrin Ribbeck‐Busch; Anja Roder; Dirk Hasse; Wietse De Boer; José Luis Martínez; Martin Hagemann; Gabriele Berg (Environmental Microbiology, 2005)
Summary In recent years, the importance of the Gram‐negative bacterium Stenotrophomonas as an opportunistic pathogen as well as in biotechnology has increased. The aim of the present study was to develop new methods for distinguishing between strains closely related to the potentially human pathogenic Stenotrophomonas maltophilia and those closely related to the plant‐associated Stenotrophomonas rhizophila . To accomplish this, 58 strains were characterized by 16S rDNA sequencing and amplified ribosomal DNA restriction analysis (ARDRA), and the occurrence of specific functional genes. Based on 16S rDNA sequences, an ARDRA protocol was developed which allowed differentiation between strains of the S. maltophilia and the S. rhizophila group. As it was known that only salt‐treated cells of S. rhizophila were able to synthesize the compatible solute glucosylglycerol (GG), the ggpS gene responsible for GG synthesis was used for differentiation between both species and it was confirmed that it only occurred in S. rhizophila strains. As a further genetic marker the smeD gene, which is part of the genes coding for the multidrug efflux pump SmeDEF from S. maltophilia , was used. Based on the results we propose a combination of fingerprinting techniques using the 16S rDNA and the functional genes ggpS and smeD to distinguish both Stenotrophomonas species.

Hydrologische Erschließung der Bundeswasserstraße Lahn von Gießen bis zur Mündung - Dennis Meißner; Norbert Busch; Dirk Schwanenberg (WASSERWIRTSCHAFT, 2005)

MHC class I restricted T cell responses tolisteria monocytogenes, an intracellular bacterial pathogen - Alyce Finelli; Kristen M. Kerksiek; S. Elise Allen; Natalia Marshall; Roberto Mercado; Ingrid Pilip; Dirk H. Busch; Eric G. Pamer (Immunologic Research, 1999)